Android Based Mobile Application for Rice Crop Management - Vijayakumar, S.; Choudhary, Anil Kumar; Deiveegan, M.; Thirumalaikumar, R.; Kumar, R. Mahender (Chronicle of Bioresource Management, 2023)
Timing of precise information is critical to minimise the wastage of agricultural inputs and as a result increased use efficiency. With the help of mobile apps, agricultural related information is disseminated at a faster rate to the farmers. The benefits of such connectivity and information flow include better crop and land management decisions besides optimizing fertilizer, seeds and water use in agriculture thus save money while reducing consumption and addition of financial benefits. Short message service (SMS) and voice record have improved the social relationship between farmers and scientist. This article provides the complete information about the various android based applications available in google play store for rice crop management